'From my point of view, my wife has recovered': A qualitative investigation of caregivers' perceptions of recovery and peer support services for people with bipolar disorder in a Chinese community. (June 2019) - Yuen, Winnie WY; Tse, Samson; Murray, Greg; Davidson, Larry
Background: Bipolar disorder (BD) is a chronic mental disorder, and family members play a key role in taking care of the affected individuals. The recovery movement has gradually transformed mental health services, for example, through the introduction of peer support services (sharing of expert-by-experience knowledge), and it has challenged the prevailing view that people with mental illness cannot recover. Aims: Through this study, the researchers explored how family caregivers in a Chinese context conceptualise recovery, how caregivers interact with peer support workers (PSWs) and how they perceive peer support services. Methods: Fourteen family caregivers from community settings participated in individual semi-structured interviews. The data were analysed through thematic analysis. Results: Family caregivers had multifaceted definitions of recovery and had various degrees of contact with PSWs. The views and experiences shared by PSWs were hope-instilling for caregivers and changed their perception of BD and their loved ones. Some limitations of PSWs were also identified. Conclusion: Social connectedness and functional outcomes were important indicators of recovery among Chinese family caregivers. Caregivers began to understand the benefits of PSWs after experiencing their services. Peer-led services could be a helpful support for both service users and family caregivers.